Quality control of uroflowmetry and urodynamic data from two large multicenter studies of male lower urinary tract symptoms. Issue 4 (18th March 2020) - Aiello, Martino; Jelski, Joseph; Lewis, Amanda; Worthington, Jo; McDonald, Charlotte; Abrams, Paul; Gammie, Andrew; Harding, Chris; Biers, Suzanne; Hashim, Hashim; Lane, J. Athene; Drake, Marcus J.
Abstract: Aim: The International Continence Society (ICS) has standardized quality control and interpretation of uroflowmetry and urodynamics. We evaluated traces from two large studies of male lower urinary tract symptoms (UPSTREAM and UNBLOCS) against ICS standards of urodynamic equipment and practice. Methods: Ten percent of uroflowmetry and urodynamics traces were selected at random from hospital sites. A data capture template was designed from the ICS Fundamentals of Urodynamic Practice checklist. Two pretrained blinded assessors extracted the data, with a third assessor to arbitrate. Departmental records of calibration checks and equipment maintenance were scrutinized. Results: Seven out of twenty‐five (28%) departments reported no calibration checks. Four sites (16%) could not provide annual service records. In 32 out of 296 (10.8%) uroflowmetry traces, findings were affected by artifact. One hundred ten urodynamic study traces were reviewed; in 11 records (10%), key pressure traces were incompletely displayed. In 30 (27.2%), reference zero was not set to atmospheric pressure. Resting pressures were outside the expected range for 36 (32.7%). Pressure drift was seen in 18 traces (16.4%). At pressure‐flow study commencement, permission to void was omitted in 15 (13.6%). Cough testing after voiding was done in 71.2%, but the resulting cough spikes were significantly different in 16.5%. Erroneous diagnosis of bladder outlet obstruction (BOO) was identified in six cases (5.5%). Conclusions: Erroneous diagnosis of BOO is a serious error of interpretation, as it could lead to unnecessary surgery. Other errors of standardization, testing, and interpretation were identified with lower risk of adverse implications. Inconsistent documentation of service records mean equipment accuracy is uncertain.